2021
DOI: 10.1038/s41467-021-23509-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic causal brain circuits during working memory and their functional controllability

Abstract: Control processes associated with working memory play a central role in human cognition, but their underlying dynamic brain circuit mechanisms are poorly understood. Here we use system identification, network science, stability analysis, and control theory to probe functional circuit dynamics during working memory task performance. Our results show that dynamic signaling between distributed brain areas encompassing the salience (SN), fronto-parietal (FPN), and default mode networks can distinguish between work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 113 publications
10
58
0
Order By: Relevance
“…The AI lacks external (layer II) and internal granular (IV) layers, which may subserve its special role of integrating information across wide-spread neuronal networks (Mesulam & Mufson., 1985;Morel et al, 2013;Wylie et al, 2015). By showing that there are distinctive patterns of oscillations for the anterior versus posterior insula that match broader cortex-wide patterns, it supports the notion that the insula is a communication hub and suggests that distinctive patterns of oscillations could play a role in allowing it to engage with other regions, such as the DMN and FPN, across a wide range of cognitive and affective tasks (Cai et al, 2016;Cai et al, 2021;Chen et al, 2016;Lamm & Singer, 2010;Sridharan et al, 2008).…”
Section: Hierarchical Organization Of Spectral Frequency and Power Of Theta And Beta Oscillations In The Human Insulasupporting
confidence: 53%
See 4 more Smart Citations
“…The AI lacks external (layer II) and internal granular (IV) layers, which may subserve its special role of integrating information across wide-spread neuronal networks (Mesulam & Mufson., 1985;Morel et al, 2013;Wylie et al, 2015). By showing that there are distinctive patterns of oscillations for the anterior versus posterior insula that match broader cortex-wide patterns, it supports the notion that the insula is a communication hub and suggests that distinctive patterns of oscillations could play a role in allowing it to engage with other regions, such as the DMN and FPN, across a wide range of cognitive and affective tasks (Cai et al, 2016;Cai et al, 2021;Chen et al, 2016;Lamm & Singer, 2010;Sridharan et al, 2008).…”
Section: Hierarchical Organization Of Spectral Frequency and Power Of Theta And Beta Oscillations In The Human Insulasupporting
confidence: 53%
“…Similar to the findings in non-human primates, MRI studies in humans have also shown subdivisions in the insula (Ghaziri et al, 2017;Morel, Gallay, Baechler, Wyss, & Gallay, 2013). Previous fMRI studies have shown functional subdivisions within the insula, as the AI was involved in task-related engagement and disengagement with the DMN and FPN across a wide range of cognitive and affective tasks (Cai et al, 2016;Cai, Ryali, Pasumarthy, Talasila, & Menon, 2021;Chen, Cai, Ryali, Supekar, & Menon, 2016;Lamm & Singer, 2010;Sridharan et al, 2008). The AI, along with the anterior cingulate cortex, are known as the salience network, Royer, & Buzsáki, 2012;Patel, Schomburg, Berényi, Fujisawa, & Buzsáki, 2013) in rodents.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations